Technical-economic prefeasibility of an olive pomace biorefinery for the main olive-growing areas of Argentina - Monetta, Pablo Miguel; Renzi, Laura Andrea; Beccaria Ibañez, Javier; Alday Poblete, Silvina Esther (University of California at Davis, Estados Unidos, 2024)
Presentación en diapositivas